The great war of our time [compact disc, unabridged] : an insider's account of the CIA's fight against terrorism--from al Qa'ida to ISIS - Morell, Michael J.; Harlow, Bill, 1950- (Hachette Audio, 2015)
The CIA's deputy director discusses the Agency's inner workings to reveal its accomplishments, mistakes, and controversies during the War on Terror while providing an assessment of ongoing threats.